2006
DOI: 10.1177/1077546306062097
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Induction Motor Faults: A Comparison of Stator Current, Vibration and Acoustic Methods

Abstract: In this paper we present the comparison results of induction motor fault detection using stator current, vibration, and acoustic methods. A broken rotor bar fault and a combination of bearing faults (inner race, outer race, and rolling element faults) were induced into variable speed three-phase induction motors. Both healthy and faulty signatures were acquired under different speed and load conditions. To address the detection capabilities of the above methods, comparisons are made in both the time and joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
66
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 23 publications
0
66
0
5
Order By: Relevance
“…Vibration and torque signal analysis for electrical fault detection has received significantly less attention in available literature due to claimed lower sensitivity, but was however shown to be feasible [8,9]. Consequently a number of authors have recently investigated WRIG winding fault detection and the reported findings demonstrate that winding fault specific spectral changes can be identified in WRIG currents [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration and torque signal analysis for electrical fault detection has received significantly less attention in available literature due to claimed lower sensitivity, but was however shown to be feasible [8,9]. Consequently a number of authors have recently investigated WRIG winding fault detection and the reported findings demonstrate that winding fault specific spectral changes can be identified in WRIG currents [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In general, fault diagnosis of an induction motor is performed by analyzing current, voltage, vibration, acoustic emission (AE), and thermal signals [2,3]. Especially, current and voltage signals have been widely used to classify abnormalities of the induction motor due to their easy signal measurement and their low cost to monitor.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of electrical drives has interested many researchers so far (Sethom and Ghedamsi, 2012;Li and Meshefske, 2006;Bindus and Vinod, 2014;Pandey et al, 2012). As provided in Thorsen and Dalva (1995), Bonnett and Yung (2008), Thorsen and Dalva (1998), the repartition of many older publications on the defects of high power asynchronous machines has changed due to the motors production conditions.…”
Section: Introductionmentioning
confidence: 99%